Calcule o valor de K, de modo que a função y=kx²-2x+3 admita -1 como zero.
a)K= 2
b)K=-5
c)K= 1/2
d)K= 1/4
Soluções para a tarefa
Respondido por
0
apenas substitua o x=-1 que fica k+2+3=0 k=-5 A)
Respondido por
1
Y = Kx2 - 2x + 3
Kx2 -2x + 3 = 0
K*(-1 ) 2 - 2*(-1 ) + 3 = 0
K + 2 + 3 = 0
K + 5 = 0
K = - 5
opção B
Kx2 -2x + 3 = 0
K*(-1 ) 2 - 2*(-1 ) + 3 = 0
K + 2 + 3 = 0
K + 5 = 0
K = - 5
opção B
Perguntas interessantes
Química,
11 meses atrás
Música,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Geografia,
1 ano atrás